CURRENT TRENDS IN THE DEVELOPMENT OF CORPORATE AGRICULTURAL ENTERPRISES - VLASENKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Entry In the agricultural sector of the regional economy, the formation of corporate-type structures is being pursued, which combines them in an integrated form, by concentrating capital, labor resources, and industrial infrastructure to achieve savings. significant effect, increased productivity and increased product sales. Integration creates receptive minds for growing the obligations of rural production, with more effective agro-industrial establishments of the corporate type, which can create a closed cycle, leading to the necessary financial capital Talent and access to long-term lending.The purpose of this publication is analysis, tracking of trends in the development, formation, and functioning of corporate agricultural enterprises based on current realities.Results. The statistics examine the nutritional characteristics, development trends and functioning in the current minds of corporate-type enterprises, such as agricultural holdings. The essence of the concept of corporation and the particularity of the creation of corporate enterprises are identified. An assessment of the development of the land fund has been carried out, and an analysis of the division of rural agricultural enterprises across the area of rural agricultural land has been carried out. The dynamics of the number of agricultural enterprises for 2008-2021 have been determined, and the dynamics of the sown area of agricultural crops has been examined. The formation of corporate systems was studied and it was determined that the greatest expansion and development was achieved by this form of corporate agricultural formations, such as agricultural holdings. The essence of agricultural holdings and the features of their formation, functioning and legal status are outlined. Named TOP 10 agricultural holdings of the region. An analysis of the positive and negative aspects of the functioning of agricultural holdings has been carried out.Visnovki. Due to the fate of the independence of the region from the global aggregate of agricultural enterprises, there was a vision of great corporate agricultural formations, such as for the development of tracts of agricultural land, the effect of scale, however The importance of innovation was reflected in significant competitive advantages. The main advantage of agricultural holdings lies in the manifestation of a synergistic effect.
Keywords: corporation; agricultural holding; integration; agricultural land; land; agricultural enterprises; corporate records